Spatiotemporal (kinematic) properties of the finalists of European Swimming Championships in butterfly stroke Trieste 2005 - Dybinska, E.; Haljand, R. (Human Movement, 2007)
Purpose. One of the control methods of swimming practice is a detailed analysis of a swimming race and its component parameters, thanks to which the level of mastery of movement technique can be assessed. The aim of the paper was to specify to what extent spatiotemporal (kinematic) parameters affect the sports result and how these parameters are represented by the best competitors in individual phases of the swimming race. Basic procedures. The paper is based on a study of the European Swimming Championships in Trieste, 2005, and analyzes men and women butterfly s troke events at distances of 50 m, 100 m and 200 m. The following spatiotemporal (kinematic) quantities were considered: s tart t ime, turning t ime, swimming velocity, finishing time, stroke rate and stroke length. To specify the differentiation between the analyzed variables, the standardization of results and Pearson linear correlation were used. Main findings. It was found that the groups of male and female competitors proved to be fairly diversified in their spatiotemporal (kinematic) quantities. The competition winners when compared with other competitors, featured better average velocity, stroke rate and efficiency. However, no competitor obtained the highest results in all analyzed factors. Conclusions. A careful observation of changes of basic swimming technique kinematic parameters and their interpretation enables diagnosis and forecast n ecessary f or p roper training d evelopment. The knowledge of individual movement t echnique parameters e nables a thorough assessment of the swimmer`s training level and makes it possible to match it with model standards.